Hydride Reduction by a Sodium Hydride–Iodide Composite. (17th February 2016) - Too, Pei Chui; Chan, Guo Hao; Tnay, Ya Lin; Hirao, Hajime; Chiba, Shunsuke
Abstract: Sodium hydride (NaH) is widely used as a Brønsted base in chemical synthesis and reacts with various Brønsted acids, whereas it rarely behaves as a reducing reagent through delivery of the hydride to polar π electrophiles. This study presents a series of reduction reactions of nitriles, amides, and imines as enabled by NaH in the presence of LiI or NaI. This remarkably simple protocol endows NaH with unprecedented and unique hydride‐donor chemical reactivity.